High-Pressure Water Jet System Treatment of Argan Nut Shell and Enzymatic Hydrolysis for Bioethanol Production - Jihane Zeghlouli; Gwendoline Christophe; Kota Ogura; Naoki Sawamura; Amine Guendouz; Cherkaoui El Modafar; Philippe Michaud; Cédric Delattre (Fermentation, 2022)
Argan nut shell represents the most generated by-product during the process of the extraction of argan oil. For the first time, argan nut shell was characterized and assessed as a new potential feedstock for bioethanol production using a combination of mechanical and enzymatic pretreatment. Argan shell samples were first disintegrated using the Star Burst system, which involves a high-pressure water jet system. Then, the pretreated argan nut shell was subjected to enzymatic hydrolysis using Viscozyme L (30 FBGU/g). Afterwards, the fermentation of the hydrolysate by Saccharomyces cerevisiae was investigated. Argan nut shell, as a feedstock plentiful in carbohydrates, conferred a high yield of saccharification (90%) and an optimal ethanol bioconversion (45.25%) using Viscozyme L (30 FBGU/g) at 2%w/v of argan feedstock.